Implementer and recipient perspectives of community-wide mass drug administration for soil-transmitted helminths in Kwale County, Kenya. - Hugo Legge; Stella Kepha; Mateo Prochazka; Katherine Halliday; Rachel Pullan; Marie-Claire; Doris Njomo (Public Library of Science (PLoS), 2020)
Soil-transmitted helminthiases (STH) are one of 17 neglected tropical diseases (NTDs) earmarked for control or elimination by 2020 in the WHO's Roadmap on NTDs. Deworming programs for STH have thus far been focused on treating pre-school and school-aged children; however, there is a growing consensus that to achieve elimination of STH transmission, programs must also target adults, potentially through community-wide mass drug administration (MDA). There is currently a gap in the literature on what components are required to deliver community-wide MDA for STH in order to achieve high intervention reach and uptake. Nested within the TUMIKIA Project, a cluster randomized trial in Kenya evaluating the effectiveness of school-based deworming versus community-wide MDA, we collected qualitative data from program implementers and recipients in eight clusters where community-wide MDA was delivered. Data collection included semi-structured in-depth interviews (n = 72) and focus group discussions (n = 32). A conceptual framework for drug distribution was constructed to help build an analysis codebook. Case memos were developed for each top-level theme. Community-wide MDA for STH was perceived as a complex intervention with key administrative and social mobilization domains. Key actionable themes included: (1) developing an efficient strategy to allocate reasonable workload for implementers to cover all targeted households; (2) maximizing community drug distributors' motivation through promoting belief in the effectiveness of the intervention and providing sufficient financial incentives; (3) developing effective capacity building strategies for implementers; and (4) implementing a context-adapted community engagement strategy that leverages existing community structures and takes into consideration past community experiences of MDAs. Transitioning from STH control to elimination goals requires significant planning and action to ensure community-wide MDA is delivered with sufficient reach and uptake. We present findings that can inform national deworming programs to increase intervention delivery capacity.